EFFECTIVE TIME PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH MENENGAH ATAS SE-KOTA PONTIANAK - Haetami, Mimi (Jurnal Visi Ilmu Pendidikan, 2020)
ABSTRACT        The study of physical education in schools is often criticized by both the school and community. The presumption that the subject of physical education as a complement, less meaningful learning, so there is the assumption that the subject of physical education is not important. This is a challenge for physical education practitioners in developing and improving the quality of learning better.         In the implementation there are still many problems in the learning of physical  education such as: [1] there is still a lot of time wasted during physical education lesson in progress, so that learning tends to be less meaningful., [2] involvement of students as a whole when lesson is not maximal, so that learners begin to feel bored in learning, [3] Utilization of learning time is still minimal, so the management of the class seemed not ready.       The purpose of this study is expected to know how much time effective in learning physical education in high school in the city of Pontianak. While the method used in this research is descriptive research method with quantitative approach, in the form of survey, with the number of samples of 5 public schools located in the city of Pontianak.        The conclusion of the calculation of the percentage of effective time of learning of learners in high school is found as follows: SMAN 1 with the proportion of time utilization (63.33%) and the total involvement of learners (83.33%); SMAN 2 with the proportion of time utilization (46.67%) and the number of students' involvement (75.00%); SMAN 3 with the proportion of time utilization (44.44%), and the number of students' involvement (85.00%), SMAN 4 proportion of time utilization (44.44%) with the total involvement of learners (61.90%), SMAN 5 with the proportion of time utilization (46.67%), and number of learner participation (45.00%). Keywords: effective time, learning